The profit of the slaughterhouses realized in the course of CT-aided selection of rabbits - Mikó, Annamária; Radnai, István; Gerencsér, Zsolt; Matics, Zsolt; Nagy, István; Szendrő, Katalin; Szendrő, Zsolt (Acta Agraria Kaposváriensis, 2010)
One of the Hungarian rabbit breeding sector’s characteristics is that almost all purchased rabbits are exported while their local commerce is minimal. Meat production is one parameter of meat quality which is continuously gaining importance. Improving the meat production of the Pannon White rabbits began in 1992 with the application of Computer Tomography (CT). The objective of the present study was to examine the efficiency of the CT-aided selection from the viewpoint of the slaughterhouses. Analysis of profitability was made using the data of our previous trials taking into account the price obtained for the whole carcass or for the meat fillet. Supposing the same price of Pannon White (P) and Hycole (H) rabbits (trial 1.) marketing the whole carcasses or the meat fillet products resulted in 19 HUF/kg and 43 HUF/kg extra incomes for the Pannon White rabbits. Supposing a slaughter weight of 2.7 kg this value is 51 and 116 HUF per individual. Comparing PÃ—P and PÃ—H genotypes (trial 2) the advantage of the PÃ—P rabbits was 38 HUF/rabbit and 78 HUF/rabbit for whole carcass or the meat fillet product. Comparing the second generation of the divergent selection for thigh muscle volume (trial 3) after 10 generations marketing the whole carcass or the meat fillet product results 68 and 216 HUF extra income per individual (average body weight 2.7 kg) at the slaughterhouse. Supposing the annual slaughter of one million rabbit as a result of the CT-aided selection can increase the profit of the slaughterhouse with 80âˆ’100 million HUF. It can be concluded that the selection based on CT data is highly advantageous for the slaughterhouses because they obtain more lean meat from a CT selected rabbit having the same body weight (ie. for which the slaughterhouse paid the same price) which results in a substantial extra income. Thus it would be worth for the slaughterhouses to pay higher price for these animals and share their extra profit with the producer. (Exchange rate between EURO and HUF is about 260–270.)
Keywords: rabbit; CT-aided selection; meat production; profit